Pengaruh Pelayanan, Kualitas Produk, Dan Lokasi Terhadap Keputusan Pembelian. (Studi Kasus Pada Indomaret Ruko Garuda Mas) - Dewangga Dwi Kharislam; Yuwita Ariessa Pravasanti; Suhesti Ningsih (Jurnal Akuntansi dan Pajak, 2022)
The purpose of this the research is to know the influence of service, product quality, and location on purchasing decisions at Indomaret Ruko Garuda Mas. This study uses three independent variables namely service, product quality and location with the dependent variable is purchasing decisions. The data in this study were collected through distributing questionnaires to 100 people who had visited Indomaret Ruko Garuda Mas as research samples. The sampling technique used is purposive sampling. The data analysis method used is quantitative analysis, namely validity and reliability tests, multiple linear regression analysis, F test, t test and the coefficient of determination. The results of this study indicate that the service, product quality, and location variables simultaneously influence purchasing decisions, this is evidenced by the significance value of the f test, which is 0.000